Comparative botanical and grassland management studies of established and restored grasslands and fallow lands - Penksza, Károly; Ifj. Viszló, Levente; Szentes, Szilárd; Stilling, Ferenc; Fűrész, Attila (Animal welfare, Ethology and Housing Systems (AWETH), 2022)
Our research was carried out in Páskom (Reznek-dűlő, Túzok-rét), located in the Zámoly basin, situated northeast of the municipality of Zámoly. The area is owned by the Pro Vértes Nature Conservation Foundation, which is significant because the Zámoly Tsz was broken up in the 1980s and was cultivated until the early 2000s. Considering that the population of the Great Bustard of the Zámolyi Basin lived there until the early 1980s, the area was restored to pasture. Based on the available data, the aim of the present work is to find out the answers to the following research questions: how does the number of species change during the different grassland establishment periods? How change the economic and conservation values of the grassland by conservation management, post-establishment mowing and grazing by Hungarian Grey Cattle? Which are the most useful grassland establishment techniques? Change of vegetation in the area was monitored in 2012 and 2020-2022. In each sample plot, 7-7 coenological surveys were carried out, giving the occurrence of species in the sample plots and their cover values. Grass species of importance for grassland management have dominated over the period, with an average cover value of over 10%. Based on the Raunkiaer life form analysis, there were no significant differences between the study areas, most of the species belonged to the perennial group. The Pignatti life form distribution already showed differences, but it is clear that the area was not grazed yet, because perennial and rosette species with creeping life forms did not reproduce. The highest rate of natural disturbance tolerance was found in the sample plots, except for the fallow sample plot, where the highest cover was already natural competitors (Festuca rupicola). In the direct-seeded plot, the highest rate of ruderal competitors was still observed in 2022. The area was mowed for 3 years which may have made significant effects on species richness in all sampling plots and fields. Several studies also confirm that mowing increases species richness in abandoned areas. Finally, among the establishment methods studied, we recommend hay transfer method, which is not only environmentally friendly, but also has the potential to achieve the highest economic benefits in the long term, as well as being of conservation value.
Keywords: relative ecological values; grassland management values; Pignatti life form system; Festuca pseudovina